VideoPlay: Playful and Social Editing of Video using Tangible Objects and Multi-touch Interaction - Taylor, Stuart; Izadi, Shahram; Ozenc, Kursat; Harper, Richard (IEEE International Workshop on Horizontal Interactive Human-Computer Systems (TABLETOP '07), 2007)
VideoPlay is a novel tabletop system for editing video using tangible objects and multi-touch interaction. It targets the unique capabilities of the Microsoft Surface platform which supports high precision multi-touch and physical object sensing and tracking. New interaction techniques are presented that allow content to be downloaded from mobile devices onto the table. Physical tiles representing video clips, transitions and effects can be assembled and locked together with the aid of embedded magnets to create new video sequences. The intention is to support playful interaction, making the process of video editing more collaborative and engaging when compared to traditional techniques.